Expression of c-erbB-2, c-myc, and c-ras oncoproteins, insulin-like growth factor receptor I, and epidermal growth factor receptor in ovarian carcinoma. Issue 10 (October 1994) - van Dam, P A; Vergote, I B; Lowe, D G; Watson, J V; van Damme, P; van der Auwera, J C; Shepherd, J H
Abstract : AIMS–To assess whether the overexpression of five dominant oncogene encoded proteins is crucial to the pathogenesis of ovarian carcinoma and whether this provides any useful prognostic information. METHODS–The expression of the insulin-like growth factor 1 receptor (ILGFR 1), epidermal growth factor receptor (EGFR), and the c-erbB-2, c-ras, and c-myc products was studied by multiparameter flow cytometry in 80 patients with epithelial ovarian cancer for whom long term follow up was available. RESULTS–Overexpression of ILGFR 1, EGFR, c-erbB-2, c-ras and c-myc was found in, respectively, nine of 80 (11%), 10 of 80 (12%), 19 of 80 (24%), 16 of 80 (20%) and 28 of 80 (35%) ovarian carcinomas. The levels of expression of ILGFR 1, EGFR, c-erbB-2 and c-ras were significantly higher in the tumours of patients with recurrent or persistent disease after chemotherapy than in the tumours of patients at initial presentation (p < 0.02). Multivariate analysis showed that residual tumour (p < 0.001), FIGO stage (p = 0.002), EGFR overexpression (p = 0.030) and previous chemotherapy (p = 0.034) were independent variables for predicting survival. CONCLUSIONS–Overexpression of these oncoproteins only occurs in a small proportion of ovarian carcinomas but may have an important role in the progression of the disease.